Production of recombinant D-allulose 3-epimerase utilizing an auto-induction approach in fermentor cultures suitable for industrial application - Lischer, Kenny; Laksmi, Fina Amreta; Nugraha, Yudhi; Az-Zahra, Fauziah; Herawan, David; Juanssilfero, Ario Betha; Wibowo, Des Saputro; Ramadhan, Kharisma Panji; Nuryana, Isa; Ali, Mohd Shukuri Mohamad (Public Library of Science, 2025)
D-Allulose 3-epimerase (DAEase) is the key enzyme catalyzing D-fructose to catalyze into D-allulose, a rare sugar in foods, which has lately drawn increasing worldwide attention owing to its possible health advantages and application as a substitute sucrose. This work focused on the development of an economical, scalable production method of DAEase by using the Escherichia coli BL21 star™ (DE3) as host expression. The research work aims to optimize the production of the enzyme through an auto-induction strategy in chemically defined media by using lactose as a natural inducer, thereby overcoming various limitations of conventional IPTG induction methods. The optimal concentration of lactose, glucose, and glycerol for maximum expression of DAEase was determined to be 1.5%, 0.125%, and 1.5%, respectively. Fermentor-scale optimization yielded a maximum amount of this enzyme with 5% inoculant, 300 rpm agitation, and 2 vvm aeration. Purification by affinity and anion exchange chromatography resulted in a sevenfold increase in specific activity with an overall yield of 12% and 43 mg of pure recombinant DAEase per liter of culture. Enzyme assays confirmed that DAEase had catalytic activity in the conversion of D-fructose to D-allulose, which was further confirmed by HPLC analysis. This optimized auto-induction-based strategy demonstrated its potential for large-scale production of DAEase in a cost-effective manner with enhanced reproducibility to meet industrial demands for synthesizing D-allulose.